Identification and characterization of polytene chromosomes of Bactrocera Papayae (Diptera: Tephritidae) - Farzana Yesmin,; Mahani Mansor Clyde, (Penerbit Universiti Kebangsaan Malaysia, 2012)
The present study constitutes a first attempt to identify the larval salivary gland polytene chromosome arms of Bactrocera papayae Drew & Hancock. This species belongs to the family Tephritidae and is commonly known as the Asian papaya fruit fly. A photographic representation of the polytene chromosomes of this species is provided and the identifying tips as well as most prominent landmarks of each polytene chromosome are presented and discussed. Each polytene nucleus consists of five long chromosomes. According to the position of centromere, the longer arm was designated as left (L) and the shorter arm as right (R). No polytenized sex chromosomes are seen, indicating that five polytene chromosomes correspond to the five autosomes of mitotic chromosomes.